Economic evaluation of monitoring virologic responses to antiretroviral therapy in HIV-infected children in resource-limited settings - Karen Schneider (2018)
Objective: Antiretroviral therapy (ART) management for HIV-infected children is critical in many resource-constrained countries. We investigated the cost-effectiveness and cost-utility of different frequencies of monitoring plasma viral load among HIV-positive children initiating ART in a resource-limited setting. Design/Methods: A stochastic agent-based simulation model was built and directly informed by a cohort of 304 HIV-infected children starting ART in Thailand between 2001 and 2009. The model simulated the expected costs and clinical outcomes over time according to different viral load monitoring frequencies and initiation of second-line therapies when appropriate. Results: The optimal frequency of viral load monitoring was found to be annual, after a single screening at 6 months. Associated costs of viral load monitoring and appropriate ART would approximately triple current treatment costs. Compared with current conditions, a single screening during the first year of ART led to a 58.4% reduction in the total person-years of virological failure with annual monitoring leading to a 76.6% reduction. The incremental cost per quality adjusted life year gained from the optimal monitoring frequency was estimated as US$ 68 084 when including costs of ART and US$ 7224 without ART costs. The estimated cost attributed to preventing 1 year of virological failure was US$ 3393 with ART costs and US$ 359 without ART costs. Conclusion: Even infrequent viral load monitoring is likely to provide substantial clinical benefit to HIV-infected children on ART. Viral load monitoring can be considered cost-effective in many resource-limited settings. However, the costs associated with second-line therapies could be a barrier to its economic feasibility. © 2011 Wolters Kluwer Health - Lippincott Williams & Wilkins.